The expression of tense, aspect, modality and evidentiality in Albert Camus's L'étranger and its translations an empirical study = L'étranger de Camus et ses traductions : questions de temps, d'aspect, de modalité et d'évidentialité (TAME) : etude empirique - Corre, Eric; Do-Hurinville, Danh Thành; Dao, Huy Linh (Linguisticae investigationes. Supplementa ;, 2020)
"This book deals with the linguistic treatment of tense-aspect-modal-evidential (TAME) expressions in translations of the French novel L'Étranger by Albert Camus into sixteen languages. It is strongly empirical in spirit, and uses the method of contrastive linguistics and multilingual comparison through the use of parallel corpora. It has five main parts: the first two offer insights into perfect and imperfect tenses in Indo-European languages; the third part shifts the focus on non Indo-European languages; the fourth part deals with modality, and the last part is more translation-oriented. These contents make this book a valuable contribution in semantic micro-typology. In terms of readership, both linguists and specialists in translation, as well as literature scholars, can benefit from the contributions presented in this book. It also relates to other usage-based, corpus-driven studies of TAME phenomena, and to monographs that take as their object of study the use of corpus linguistics in translation studies"--